Cancer chemoprevention – application perspectives in prophylactics and therapy - Cyranka, Małgorzata; Kapka, Lucyna; Rzeski, Wojciech (Polish Journal of Public Health, 2009)
Cancer chemoprevention is defined as the use of natural, synthetic, or biological and chemical agents to reverse, suppress, or prevent either the initial phase of carcinogenesis or the progression to invasive cancer in high-risk populations. Several chemopreventive agents (including tamoxifen) are proved to be effective in preventing the development of cancer, while several remain just as dietary restrictions. Chemopreventive agents have been reported to interfere with a specific stage of the carcinogenesis and different mechanisms involved in anticancer activity have been described. This article summarises agents that have a chemopreventive potential against cancer, as well as these ones which are already in clinical use against cancer. This review will also highlight current clinical research in chemoprevention.